Evaluation of Associative Effects on Degradability, Fermentation Parameters, and In Vitro Methane Production as a Result of Variation in the Ruminants Diets Constituents - Danielle Ferreira Baffa; Tadeu S. Oliveira; Alberto Magno Fernandes; Michele Gabriel Camilo; Ismael N. Silva; Elon Souza Aniceto; José Ribeiro Meirelles Júnior; Elvanio José Lopes Mozelli Filho (Grasses)
This study aimed to investigate the effect of different forage sources and forage-to-concentrate ratios on digestibility, energy concentration, fermentation parameters, and in vitro estimate of methane. The experiment was carried out in a completely randomized design using a 3 × 6 factorial arrangement with three forages varying the chemical composition (pineapple crop waste silage [PS], corn silage [CS], and Tifton hay [TH]) associated with concentrate feed (C) in six combinations, using triplicates for each ratio. We evaluated in vitro digestibility, metabolizable and net energy, pH, redox potential, volatile fatty acids (VFA), and methane production. The in vitro neutral detergent fiber digestibility (IVNDFD) decreased (p = 0.0011) with the inclusion of concentrate. It was also affected by the forage source, but this fact was only observed in CS up to the 50:50 ratio. In TH, this fact occurred from the 80:20 ratio, and this behavior was not observed in the PS. Data on methane production, VFA, and fermentation parameters varied according to forage source and concentrate inclusion. In conclusion, the inclusion of concentrate reduces methane production, increasing the system’s energy contribution. Overall, the different forage sources and the inclusion of concentrate change digestion and fermentation parameters.